Praktik Akuntansi Keberlanjutan dalam Pengelolaan Pariwisata Pantai Pasir Panjang: Sebuah Tinjaun Nilai Budaya Masyarakat Lokal - Godensia Baina; Maria Febriani Dhone; Yufentus Ngenta; Yohanes Pemandi Lian (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the implementation of sustainable accounting practices in the management of Pasir Panjang coastal tourism by examining how local cultural values and community personality influence sustainability-driven decisions. Using a qualitative approach, data were collected through interviews, field observations, and documentation analysis involving local community members, tourism actors, and village government representatives. The findings indicate that sustainable accounting is not only understood as an administrative or financial reporting system, but also as a framework shaped by cultural norms, collective identity, and local wisdom. Elements such as communal responsibility, environmental awareness, and traditional stewardship practices significantly contribute to how sustainability initiatives are planned, recorded, and evaluated. Furthermore, the personality traits of the local community—such as openness, cooperation, and strong social cohesion—play an essential role in ensuring inclusive participation and shared accountability. This study concludes that integrating cultural values and community character enhances the effectiveness of sustainable accounting practices in coastal tourism management and encourages long-term environmental and socio-economic resilience.